Sequência didática acerca do descarte de pilhas e baterias: com o uso da metodologia da problematização - SANTOS, Charles Lima dos (Universidade Federal do Pará, 2022)
The present work entitled "Didactic Sequence About the Disposal of Batteries and Batteries: using the problematization methodology", which aimed to elaborate, apply and validate a didactic sequence, which aims to promote the teaching of Environmental Sciences, with a focus on the proper disposal of Batteries. The didactic sequence proposed an alternative for the promotion of teaching considering local knowledge, enabling the student to learn effectively. The activities were carried out through the Interactive Teaching System (SEI\SEDUC), which works with a classroom teaching methodology with technological mediation. The work was intended to answer questions such as: What is the importance of batteries in their communities and when discarded inappropriately they can cause damage to the environment and human health. As an educational product of this dissertation, a Guidance Booklet was prepared for the application of the Didactic Sequence entitled "Orientation Booklet", which went through the validation process to ascertain its potential as a didactic product. The results of the validation stage indicated that DS enabled the promotion of environmental educational practice, in addition to awakening and encouraging students to build critical and reflective knowledge. And regarding its general evaluation, the results showed that the validation carried out with the educators (Judges), shows a good acceptance with 97% approval, confirming that the didactic sequence enhances the teaching-learning process and is characterized as an instrument for the formation of socio-environmental citizens, in addition to disseminating the Teaching of Environmental Sciences and Environmental Education, contemplating the objective of the work.